SISTEM INFORMASI RESERVASI GEDUNG OLAHRAGA BERBASIS UNIFIED MODELLING LANGUAGE (UML) - Fasira, Ira (Computing Insight : Journal of Computer Science, 2025)
The sports hall reservation information system is a system designed to manage sports facility bookings efficiently and in an organized manner. With the advancement of digital technology, sports facility reservations, which were previously done manually, can now be simplified through a computer-based system. This study aims to design and develop an information system that allows users to make sports hall reservations online. The system is intended to reduce schedule recording errors, improve time and facility usage efficiency, and provide convenience for users in making reservations. In addition, this research also discusses how this system can be integrated with payment technologies to support digital transactions. The results of this study are expected to provide a positive contribution to the management of sports facilities in a more effective and transparent manner.